Comprehensive Utilisation and Performance Optimisation of Agro-electricity and Agro-photovoltaic Complementary Systems in Agricultural Production - Si, Yehua; Wang, Yiding; Cao, Yihao; Si, Delin (Transactions on Economics, Business and Management Research, 2024)
Agroelectricity agro-photovoltaic (APV) complementary systems are increasingly attracting attention in the field of agricultural production as a way of integrating and utilising renewable energy resources. The aim of this study is to investigate the integrated utilisation and performance optimisation of agro-electricity agro-photovoltaic (AEPV) systems in agricultural production in order to improve the efficiency of agricultural production, conserve energy resources, and protect the environment. The integrated utilisation section explores the application of agroelectricity agro-photovoltaic systems in different types of agricultural production, emphasising the importance of integrated energy utilisation strategies to improve energy and economic efficiency. The Performance Optimisation Methods and Strategies section describes optimisation methods for system operation, equipment performance, energy dispatch and storage to improve system performance and reliability. The section on sustainability and environmental impacts emphasises the environmental friendliness and sustainability of agropower agro-photovoltaic systems, and discusses related environmental protection strategies and social responsibility. The research and application of agro-power agricultural and photovoltaic complementary systems are expected to bring more sustainable and cost-effective solutions to agricultural production.